2013
DOI: 10.11648/j.jim.20130204.11
|View full text |Cite
|
Sign up to set email alerts
|

Public Procurement of Winter Road Maintenance Services Based on EU Procurement Directive − Lessons from Sweden

Abstract: Public procurement of road maintenance services, particularly in cold regions is not an easy task in order to satisfy road-users during winter. Road-users' dissatisfaction, complaint and pressure can usually be considered as major factors for having more accessible and safe roads during winter. These pressures have contributed and led to an increasing critical approach focusing on public procurement of these services after some harsh winters in the recent years in Sweden with traffic disruption and delay as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Lessons learned are, in this article, defined as lessons drawn from individuals’ own experiences through feedback processes in a purposively chosen manner (Abdi, Lind, & Birgisson, ; Abdi et al, ; Le Coze, ; Salmon et al, ; Spiekermann et al, ). Lessons learned is a key component for better understanding problems, and ultimately for finding the best practices or solutions (Abdi et al, , ; Le Coze, ; Salmon et al, ; Spiekermann et al, ). Scholars such as Leveson (), Le Coze (), Salmon et al (), and Spiekermann et al () argue that loops of feedback and learning are rather complex, involving many actors and levels of society.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Lessons learned are, in this article, defined as lessons drawn from individuals’ own experiences through feedback processes in a purposively chosen manner (Abdi, Lind, & Birgisson, ; Abdi et al, ; Le Coze, ; Salmon et al, ; Spiekermann et al, ). Lessons learned is a key component for better understanding problems, and ultimately for finding the best practices or solutions (Abdi et al, , ; Le Coze, ; Salmon et al, ; Spiekermann et al, ). Scholars such as Leveson (), Le Coze (), Salmon et al (), and Spiekermann et al () argue that loops of feedback and learning are rather complex, involving many actors and levels of society.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In 2013, STA was the single largest publicly procurement agency in Sweden, with 21 percent of all public procured contracts (SCA, ). The STA argued that the process of a complete outsourcing of operation and maintenance, design and construction would lead to a more efficient administrative client organization (Abdi et al, ). The aim was also to increase the pace of innovation and to improve production (Abdi et al, ).…”
Section: Case‐study Setting—the Sta and Pppmentioning
confidence: 99%
“…Winter road maintenance services are bundled with other road maintenance services into Area Maintenance Contracts (AMC). Abdi, Lind & Birgisson (2013b) discuss whether this kind of bundled contract is the best option.…”
Section: Contract Typementioning
confidence: 99%
“…Its main focus is to provide deeper knowledge and understanding of the payment mechanism for winter maintenance tasks in Sweden that are integrated in more comprehensive contracts and bundled with other road maintenance services. As the earlier studies revealed (Abdi, Lind & Birgisson, 2013b), several road maintenance services are bundled in a questionable manner in current Swedish road maintenance contracts. Focusing on the payment mechanism and the possibilities of improving it, the general conclusion and recommendations are as follows: From a risk allocation perspective, the combination of a fixed part and a weather dependent part seems to be the rational choice.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation